Management ecosystems restoration plans for coastal villages: Case Study Gresik and Malang Regency, East Java Province, Indonesia - ., Rudianto; susilo, Edi; ., Supriyatna (Advances in Social Sciences Research Journal, 2017)
The Villages on the coastal region are currently experiencing severe environmental damage caused by human activities and natural processes. Thus, it required a solution to solve the problem in coastal areas. The coastal area is a unique area and with the presence of mangrove forests to absorb carbon in large enough quantities. However, due to mangrove ecosystems and other ecosystems damaged, mangrove cannot be optimal to absorb carbon. Therefore, research is needed to determine what the best solution to manage ecosystem coastal areas towards restoration. The purpose of this study is to make an ecosystem restoration plan for coastal villages to improve the ability of mangroves to absorb carbon. Such plan will use the village government as a technical guidance together with local people to restore degraded mangrove. Besides, the second objective to be achieved is to develop appropriate institutional plan for deploying the coastal ecosystem restoration. The method used is using Partial Least Square (PLS). PLS regression is a recent technique that generalizes and combines features from principal component analysis and multiple regression. Analytical Hierarchy Process (AHP) which is used to build the institutional model that corresponds to the characteristics of coastal communities to conduct ecosystem restoration plan. The results of this research is to produce findings about the ecosystem restoration plan for coastal village and the local institution that is responsible to carry out ecosystem restoration plan .